Photocatalytic Reduction of Copper(II) over Semiconducting Powder - Verma, Vijay; Desai, Anil; Dwivedi, V.R. (Asian Journal of Chemistry, 2010)
Photocatalytic reduction of copper(II) over semiconducting iron(III) oxide was carried out. The progress of reaction was observed spectrophotometrically. The effect of variation of different parameters like pH, concentration of copper(II), amount of photocatalyst, particle size, light intensity, etc. on the rate of photocatalytic reduction was observed. A tentative mechanism for this reduction has been proposed.